Asupan Zat Besi, Vitamin C, Pengetahuan Gizi Kaitannya dengan Kejadian Anemia Remaja Putri di Bantul, Daerah Istimewa Yogyakarta : Iron and Vitamin C Intake, Nutritional Knowledge in Relation to the Incidence of Anemia in Adolescent in Bantul, Special Region of Yogyakarta - Agil Dhiemitra Aulia Dewi; Faurina Risca Fauzia; Tri Dyah Astuti (Amerta Nutrition, 2022)
Background: Female adolescents are ten times more likely to experience anemia than male adolescents because they experience menstrual bleeding every month, low iron and vitamin C intake, and lack of knowledge about iron deficiency anemia. Adolescent anemia is also caused by a lack of knowledge about balanced nutritional intake. Bantul is ranked second in adolescent anemia in DIY. Objectives: This study aims to analyze the relationship between nutritional knowledge regarding anemia, vitamin C intake, and iron intake of female adolescents in Bantul, Yogyakarta Special Region, Indonesia. Methods: This research is an observational study with a cross-sectional design. The research using cluster random sampling. The clusters that were randomly selected to be studied were 6 out of 17 districts. In each sub-district cluster, 5 SMA and 3 SMP were randomly selected. The study was conducted at Bantul Middle School and High School with female adolescents aged 13-18 years who were randomly selected from all classes from January to September 2022 with a sample size of 186 people. Primary data consisted of Fe and Vitamin C intake using the Semi-Food Frequency Questionnaire, nutrition knowledge using a validated questionnaire, and Hb levels using a capillary blood rapid test. The data were then tested statistically using STATA software with the Correlation Test. Results: From this study, 186 female adolescent respondents were obtained with 36 (19.35%) respondents having anemia, 150 (80.65%) not anemia. The median intake of iron for female adolescents was 12.5 mg/dl, the median vitamin C for female adolescents was 57.4 mg/dl, and respondents with good nutrition knowledge were 71 people, 115 people with poor knowledge. Intake of Fe, Vitamin C, and nutritional knowledge related to anemia were not significantly related to anemia in female adolescents in Bantul, DIY (P>0.05). Conclusions: Nutritional knowledge regarding anemia, intake of Fe, and Vitamin C were not significantly related to anemia of female adolescents in Bantul, DIY, but intake of Fe and vitamin C was mostly still less than nutritional requirements.